1187 Adapting Postgraduate Anatomy Education During The COVID-19 Pandemic. (12th October 2021) - Fletcher, P; Salau, E; Wray, C
Abstract: Aim: A solid understanding of anatomy and its application is crucial to the development of safe surgeons. Cadaveric dissection has traditionally been the gold standard for learning anatomy however the disruption of anatomy teaching from the COVID-19 pandemic has led to a shift in methods for teaching both undergraduate and postgraduate students. We sought to design, deliver and evaluate a virtual MRCS anatomy revision course for doctors led by anatomy demonstrators. Method: A series of six high yield revision sessions on the anatomy of the abdomen and pelvis, upper limb, lower limb, thorax and head and neck were organised on a virtual platform. The course was advertised on social media targeting groups for doctors. These sessions were taught by a senior anatomy demonstrator and previous examiner for the MRCS. This was followed by a series of interactive single best answer questions. The answers were then discussed in a subsequent session facilitated by current junior anatomy demonstrators. Feedback on student satisfaction, relevance and content of each session was collated. Results: Online feedback was completed by 263 students and was universally positive. Our results highlight the relevance of the sessions for doctors preparing for both MRCS part A and B examinations. Our aim is to develop this teaching series to create an environment where postgraduate learners feel supported and can build on pre-existing knowledge. Conclusions: Virtual anatomy teaching can be a sustainable method of supporting the learning process of doctors preparing for surgical examinations, complementing independent study, virtual dissection and hands on cadaveric dissection.